2022
DOI: 10.3390/ma15020401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ornamental Stone Waste Incorporation on the Rheology, Hydration, Microstructure, and CO2 Emissions of Ordinary Portland Cement

Abstract: The ornamental stone industry generates large amounts of waste thus creating environmental and human health hazards. Thus, pastes with 0–30 wt.% ornamental stone waste (OSW) incorporated into ordinary Portland cement (OPC) were produced and their rheological properties, hydration kinetics, and mechanical properties were evaluated. The CO2 equivalent emissions related to the pastes production were estimated for each composition. The results showed that the paste with 10 wt.% of OSW exhibited similar yield stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…The four main stages of the Portland cement hydration process can be identified in Figure 5, namely: (i) initial, (ii) induction, (iii) acceleration, and (iv) deceleration periods [56]. The main heat flow peak of WC pastes occurred at approximately 7.3 h. Note that this induction period is typically shorter compared to grey cement pastes, as indicated by the results reported by Scolaro et al [57]. The authors observed that the main heat flow peak for a grey PC paste with a water-to-cement ratio (w/c) of 0.45 and a superplasticizer (SP) content of 0.025 wt.% is around 10 h. Similarly, the results reported by de Matos et al [58] showed that the main heat flow peak of a cement paste with a w/c of 0.4 and grey Portland cement without SP occurred approximately at 12 h. The isothermal calorimetry results also indicate that the partial replacement of WC with Nb 2 O 5 percentages up to 2.0 wt.% does not affect the heat flow and the cumulative heat of the pastes.…”
Section: Isothermal Calorimetrymentioning
confidence: 63%
“…The four main stages of the Portland cement hydration process can be identified in Figure 5, namely: (i) initial, (ii) induction, (iii) acceleration, and (iv) deceleration periods [56]. The main heat flow peak of WC pastes occurred at approximately 7.3 h. Note that this induction period is typically shorter compared to grey cement pastes, as indicated by the results reported by Scolaro et al [57]. The authors observed that the main heat flow peak for a grey PC paste with a water-to-cement ratio (w/c) of 0.45 and a superplasticizer (SP) content of 0.025 wt.% is around 10 h. Similarly, the results reported by de Matos et al [58] showed that the main heat flow peak of a cement paste with a w/c of 0.4 and grey Portland cement without SP occurred approximately at 12 h. The isothermal calorimetry results also indicate that the partial replacement of WC with Nb 2 O 5 percentages up to 2.0 wt.% does not affect the heat flow and the cumulative heat of the pastes.…”
Section: Isothermal Calorimetrymentioning
confidence: 63%
“…The global cement industry is looking for experimental ways to develop cements that require less energy in their manufacture, degrade the environment less due to the high consumption of mineral resources and emit less polluting gases into the atmosphere, which contribute almost 7% of global CO 2 emissions (2.5 Gt/year), aggravating global warming and its consequences [ 1 , 2 , 3 ]. In addition, the industry is facing challenges such as increasing demand for cement and, at the same time, limited limestone reserves and increasing carbon taxes [ 4 ]. The so-called circular economy is emerging as an environmental and economic concept that aims to keep the value of products, materials and resources (water, energy, etc.)…”
Section: Introductionmentioning
confidence: 99%